Does India need national child mortality surveillance project to reduce child mortality? An opportunity from National Polio Surveillance Project (NPSP) - P Brahmapurkar Kishor (Wolters Kluwer Medknow Publications, 2017)
In 2015, India had 20 percent share of global under-five deaths (1.2 million), highest number of deaths in the world. In the era of Sustainable Development Goal (SDG), to accomplish goal 3, target 3.2 to reduce child mortality to 25 per 1,000 live births, India needs to accelerate to achieve the same. India was taken off from the list of polio endemic countries by World Health Organization in February 2012. In 1997 the National Polio Surveillance Project (NPSP) was established as a joint partnership between the World Health Organization and the Ministry of Health and Family Welfare (MoHFW), Government of India. As in Polio eradication program interaction between the health care providers and Surveillance Medical Officer (SMO), had provided the foundation for successful Acute Flaccid Paralysis (AFP) surveillance, same opportunity can be used for every child death. Each child death reported by reporting unit (RU) needs to be investigated in case investigation form (CIF) and the factors related to continuum of care for maternal, newborn and child health whichever responsible for child death needs to be identified for action. Another aim of this project will be to capture each and every child death occurring in the district and identifying the high risk blocks and accordingly training of health workers and private practitioner can be undertaken for capacity building. The feedback of factors identified for child death can be given to health officers of concerned district and same can be discussed in District Task Force meeting, so appropriate corrective action is initiated; also same can be reviewed at regional, state and national level meetings. National Child Mortality Surveillance Project can take the advantage of network of SMO already available with NPSP along with training modules and forms.